Pengembangan Media Pembelajaran Berbasis Video pada Mata Pelajaran Dasar Listrik dan Elektronika - Syahrul Ihsan; Ahyanuardi Ahyanuardi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2021)
Media is an important component to stimulate the mind and encourage the learning process. The background of the implementation of this research is the use of media that has not supported the implementation of good learning and helps students while learning from home. This can be seen from the students' understanding of the subject matter which is lacking and the minimum number of students doing the lesson. The purpose of this research is to produce video-based learning media that are categorized as valid and practical that can help students in online learning. The research method used is Research and Development (R&D). The development model used is the 4 D model which consists of 4 stages, namely Define, Design, Develop, Desseminate, developed by Thiagarajan. The assessment was carried out by a team of validators consisting of material experts and media experts, while practicality was assessed by the subject teacher. The results of the research obtained are video-based learning media based on the assessment of the material experts getting a valid category seen from the content and learning aspects. Meanwhile, media eligibility based on media experts is categorized as valid. The practicality assessment that was assessed by the subject teacher resulted in a very practical category. In conclusion, the resulting learning videos are valid and practical so that students can use them to support learning from home.